Chapter Sea level measurements in Mediterranean coast - BENINCASA, FABRIZIO (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Travels for geographical studies made it necessary, to establish elevations height, to refer all the heights to same surface to which to attribute the zero level, to compare results. At first sea surface was thought, but it is neither the same nor constant throughout the Earth and it varies over time. From 17th century measure protocols were proposed, but only in 19th century, using tide gauges with automatic recording, reliable measures series were obtained to establish a methodology to define tide level zero. From that moment procedures and devices improved to current satellite instruments